Keterlaksanaan Program Literasi SD Mi Muhajirin Duri - Fathur Risky; Putri Rahmayanti; Riska Molinda; Shintia Ramadani; Febrina Dafit (Lembaga Pengembangan Kinerja Dosen, 2023)
Reading is one of the most important functions in life. All learning processes are based on reading ability. With the ability to read that is entrenched in every child, the level of success in school and in community life will open up opportunities for success in a better life. The low reading literacy of our nation causes our Human Resources to be uncompetitive due to the lack of mastery of science and technology, as a result of the low interest and ability to read and write. Reading and writing have not become a necessity of life and have not become a national culture. After conducting various observations and interviews, we found that the GLS at Mi Muhajirin Elementary School is expected to create an educational ecosystem in SD that is literate. Implementation of the MI Muhajirin School Literacy Movement through the following activities: 1. Read a book every time before learning/beginning of learning begins at least 15 minutes. 2. Increased literacy at least 15 minutes before learning. 3. Singing folk songs. This means that students' interest in reading has increased after the implementation of the School Literacy Movement (GLS) this is proven in the learning process as in the learning process students are more active in class both in debriefing with the teacher and in discussions.